A Promising MM–Fe–Al–Ga–B Permanent Material with Substantially Boosted Magnetic Performance - Wang Chen; Shaoqing Ren; Jiaying Jin; Liang Zhou; Bo Xin; Mingjing Zhao; Mengfan Bu; Xu Li; Chen Wu; Mi Yan (Advanced Science)
Abstract Exploiting the potential of mischmetal (MM, La–Ce–Pr–Nd mixture containing ≈80 wt% La–Ce) based MM–Fe–B permanent material as an advantageous alternative for the current Nd–Fe–B is intriguing, whereas remains an arduous quest due to the drastically deteriorated magnetic performance. Herein, a facile two‐step strategy is proposed that Al‐doping towards high maximum energy product (BH)max with the subsequential grain boundary diffusion processing (GBDP) toward high coercivity Hcj, i.e., a representative 0.7 wt% Al doping and Nd/Pr‐based GBDP yields the record‐high Hcj = 10.14 kOe and (BH)max = 28.02 MGOe for the MM–Fe–Al–Ga–B sintered magnets. Appropriate Al‐doping plays a pivotal role in accelerating the La/Ce segregation in the LaCe‐rich RE–(Al, Ga), La‐rich RE6(Fe, Al, Ga)14, and Ce‐rich REFe2 intergranular phases, resulting in enhanced intrinsic and extrinsic magnetism. The following Nd/Pr‐based GBDP generates large quantities of RE6(Fe, Al, Ga)14 phase in triple junctions and grain boundaries, together with continuous Nd/Pr‐rich magnetically hardening shell, finally harvesting the substantially boosted magnetic performance. This demonstration marks a clear picture of the two‐step strategy towards fully utilizing the abundant MM resources, and overcoming the long‐standing difficulty of applicable MM–Fe–B permanent material for industrialization.